Unique Contribution of Visually Impaired Educators in Teaching Sighted Students in South Asia - Rony, M.R. (University of Jaffna, 2025)
This paper aims to highlight the contributions of the visually challenged educators in transforming the field of teaching English as a Second Language (ESL) by drawing from the unique experiences of a visually impaired teacher in South Asia. The study has its provenance in my own experiences as a completely visually impaired educator in a Government Teachers’ Training College in Bangladesh, and hence the study is an empirical exploration into the challenges and also the opportunities faced by a visually challenged teacher instructing sighted students. Although several studies have been conducted on classes taught by visually impaired teachers, those are chiefly focused on the issues faced by the sighted learners in terms of inclusive educational practices; the challenges and insights of the visually impaired tutors are rarely addressed. As such, this paper aims to bridge that gap by showcasing how visually impaired tutors bring in unprecedented pedagogical perspectives that are not only essential but also effective in fostering an empathetic learning environment and encouraging creative problem solving. In light of the personal narrative on how these challenges shaped the author’s own teaching practices, this paper intends to extrapolate on how visually challenged educators globally can redefine the traditional roles of a teacher through the integration of assistive technology and adaptive teaching strategies, thereby adding newer dimensions to what it means to be a teacher. Being an empirical narrative, the implications of this study with regards to inclusive education through the incorporation of Assistive Technologies are rendered greater credibility. The results showed that visually impaired teachers not only improve the learning landscape for a diverse set of students, they also partake in dehegemonizing teaching methods from Western and colonial frameworks by formulating unique solutions that are better suited to address issues in South Asian schools. This paper, therefore, invites a rethinking of institutional frameworks that support visually impaired educators and recognize their distinctive contribution in shaping a more inclusive and accessible educational system in South Asia.
Keywords: Autoethnography; Visually impaired educators; Inclusive education; ESL teaching; Assistive technology; Classroom management; South Asia; Bangladesh